AB0816 Eliciting Patients' Preferences for Osteoporosis Drug Treatment: A Cross-European Discrete Choice Experiment. (10th June 2014) - Hiligsmann, M.; Dellaert, B.; Dirksen, C.; van der Weijden, T.; Watson, V.; Bours, S.; Goemaere, S.; Reginster, J.-Y.; Roux, C.; McGowan, B.; Silke, C.; Whelan, B.; et al.
Abstract : Background: The patient's perspective is becoming increasingly important in clinical and policy decisions. Information about what patients prefer, and how they value various aspects of a health intervention can be useful when designing and evaluating health care programs and could help health professionals to improve disease management. Objectives: To evaluate the preferences of European patients with, or at risk of, osteoporosis for medication attributes, and to establish how they trade between these attributes Methods: A discrete choice experiment was conducted using a questionnaire in Belgium, France, Ireland, Spain, Switzerland and United Kingdom. Patients were asked to choose between two hypothetical unlabelled drug treatments (and an opt-out option) that vary in several attributes: efficacy in reducing the risk of fracture, type of potential common side-effects, mode and frequency of administration and out-of-pocket costs (only in countries with patients' contribution on the cost of treatment). An efficient design was used to construct the treatment option choice sets and a mixed logit model was used to estimate patients' preferences. Results: A total of 1, 124 patients completed the experiment, with at least 100 patients per country. As expected, in all countries, patients preferred treatment with higher effectiveness and lower cost was preferred in the three countries in which a cost-attribute was part of the experiment. In all countries, patients preferred 6-monthly subcutaneous injection over weekly oral tablets. In most countries, patients also preferred monthly oral tablet and yearly intravenous injections over weekly oral tablets. Patients disliked being at risk of gastro-intestinal disorders more than being at risk of skin reactions and flu-like symptoms. There were significant differences between countries for only some levels of attributes, and we found in all countries a significant variation in preferences across the sample for most attributes. Conclusions: This study suggests that the preferences of patients for osteoporotic drug therapy did not substantially differ between six European countries. Only for levels of some attributes, significant differences were observed. The heterogeneity of preferences across each country highlights the potential importance of clinical decision-making taking individual preferences into account to improve osteoporosis care. Acknowledgements: This study was funded by Amgen Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4055